Calculation of the Stability of the IS6110 Banding Pattern in Patients with Persistent Mycobacterium tuberculosis Disease - Warren, R. M. (American Society for Microbiology, 2002)
The interpretation of molecular epidemiologic data of Mycobacterium tuberculosis infection is dependent on the understanding of the stability and evolutionary characteristics of the DNA fingerprinting marker used to classify clinical isolates. This study investigated the stability of the IS6110 banding pattern in serial tuberculosis isolates collected from patients resident in an area with a high incidence of tuberculosis. Evolutionary changes were observed in 4% of the strains, and a half-life (t(1/2)) of 8.74 years was calculated, assuming a constant rate of change over time. This rate may be composed of a high rate of change seen during the early disease phase (t(1/2) = 0.57 years) and a low rate of change seen in the late disease phase (t(1/2) = 10.69 years). The early rate probably reflects change occurring during active growth prior to therapy, while the low late rate may reflect change occurring during or after treatment. We demonstrate that the calculation of these rates is strongly influenced by the time interval between onset of disease and sputum sampling. These calculations are further complicated by partial replacement of the original strain population, resulting in the sporadic appearance of clonal variants in sputum specimens. Therefore, the true extent of genetic diversity may be underestimated within each host, thereby influencing molecular epidemiological data used to establish transmission chains.